Satellite radiance data assimilation for binary tropical cyclone cases over the western North Pacific. (13th April 2017) - Choi, Yonghan; Cha, Dong‐Hyun; Lee, Myong‐In; Kim, Joowan; Jin, Chun‐Sil; Park, Sang‐Hun; Joh, Min‐Su
Abstract: A total of three binary tropical cyclone (TC) cases over the Western North Pacific are selected to investigate the effects of satellite radiance data assimilation on analyses and forecasts of binary TCs. Two parallel cycling experiments with a 6 h interval are performed for each binary TC case, and the difference between the two experiments is whether satellite radiance observations are assimilated. Satellite radiance observations are assimilated using the Weather Research and Forecasting Data Assimilation (WRFDA)'s three‐dimensional variational (3D‐Var) system, which includes the observation operator, quality control procedures, and bias correction algorithm for radiance observations. On average, radiance assimilation results in slight improvements of environmental fields and track forecasts of binary TC cases, but the detailed effects vary with the case. When there is no direct interaction between binary TCs, radiance assimilation leads to better depictions of environmental fields, and finally it results in improved track forecasts. However, positive effects of radiance assimilation on track forecasts can be reduced when there exists a direct interaction between binary TCs and intensities/structures of binary TCs are not represented well. An initialization method (e.g., dynamic initialization) combined with radiance assimilation and/or more advanced DA techniques (e.g., hybrid method) can be considered to overcome these limitations. Key Points: Satellite radiance data assimilation is effective in improving track forecasts of binary tropical cyclones Improved forecasts of environmental fields result in reduced track errors for binary tropical cyclones Positive effects of satellite radiance data assimilation can be limited when a direct interaction between binary tropical cyclones exists